Structural analysis of the manganese transport regulator MntR from Bacillus halodurans in apo and manganese bound forms - Lee, Myeong Yeon (PLoS One, 2019)
The manganese transport regulator MntR is a metal-ion activated transcriptional repressor of manganese transporter genes to maintain manganese ion homeostasis. MntR, a member of the diphtheria toxin repressor (DtxR) family of metalloregulators, selectively responds to Mn(2+) and Cd(2+) over Fe(2+), Co(2+) and Zn(2+). The DtxR/MntR family members are well conserved transcriptional repressors that regulate the expression of metal ion uptake genes by sensing the metal ion concentration. MntR functions as a homo-dimer with one metal ion binding site per subunit. Each MntR subunit contains two domains: an N-terminal DNA binding domain, and a C-terminal dimerization domain. However, it lacks the C-terminal SH3-like domain of DtxR/IdeR. The metal ion binding site of MntR is located at the interface of the two domains, whereas the DtxR/IdeR subunit contains two metal ion binding sites, the primary and ancillary sites, separated by 9 Å. In this paper, we reported the crystal structures of the apo and Mn(2+)-bound forms of MntR from Bacillus halodurans, and analyze the structural basis of the metal ion binding site. The crystal structure of the Mn(2+)-bound form is almost identical to the apo form of MntR. In the Mn(2+)-bound structure, one subunit contains a binuclear cluster of manganese ions, the A and C sites, but the other subunit forms a mononuclear complex. Structural data about MntR from B. halodurans supports the previous hypothesizes about manganese-specific activation mechanism of MntR homologues.